2001
DOI: 10.1111/j.1471-0528.2001.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration in maternity care: a randomised controlled trial comparing community‐based continuity of care with standard hospital care

Abstract: Objective To test whether a new community-based model of continuity of care provided by midwives and obstetricians improved maternal clinical outcomes, in particular a reduced caesarean section rate. Design Randomised controlled trial.Setting A public teaching hospital in metropolitan Sydney, Australia.Sample 1089 women randomised to either the community-based model (n 550) or standard hospital-based care (n 539) prior to their ®rst antenatal booking visit at an Australian metropolitan public hospital.Main out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…In a randomised controlled trial comparing community based care with standard hospital care a significant difference in caesarean section rates was found (13.3% v 17.8% respectively) 29. Planning a home birth30 or booking for care at a midwife led birth centre is also associated with lower operative delivery rates.…”
Section: Philosophy Of Carementioning
confidence: 99%
“…In a randomised controlled trial comparing community based care with standard hospital care a significant difference in caesarean section rates was found (13.3% v 17.8% respectively) 29. Planning a home birth30 or booking for care at a midwife led birth centre is also associated with lower operative delivery rates.…”
Section: Philosophy Of Carementioning
confidence: 99%
“…Women who had midwife-led models of care were less likely to use regional analgesia (RR 0.81, 95% CI 0.73–0.91) or have an instrumental birth (RR 0.86, 95% CI 0.78–0.96), and were more likely not to use intrapartum analgesia/anaesthesia (RR 1.16, 95% CI 1.05–1.29), experience spontaneous vaginal birth (RR 1.04, 95% CI 1.02–1.06), feel in control during labour and childbirth (RR 1.74, 95% CI 1.32–2.30), and initiate breastfeeding (RR 1.35, 95% CI 1.03–1.76) [22]. Three trials have shown that midwifery continuity of care significantly reduced the CS rate: one small trial in Canada [28] and two in Australia, the most recent being published in 2012 [29,30]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they were less likely to experience foetal loss before 24 weeks’ gestation and their babies were more likely to have a shorter length of hospital stay. Even if there were no statistically significant differences in the overall estimates for caesarean births [10], two studies included in the Cochrane review, one conducted in Canada [28] and one in Australia [29], observed a lower CS rate for the midwife or midwife and obstetrician model of care compared to the standard physician-led model.…”
Section: Discussionmentioning
confidence: 99%